Comparing C3, 4, and 5 nerve root block and interscalene with intermediate cervical plexus block in diaphragmatic motion for clavicle surgery - Qi Li; Xiaoxiao Chen; Junde Han; Yaming Xie; Chentao Gu (Scientific Reports)
Abstract Regional anesthesia is a popular method for surgical anesthesia in clavicular surgery. Selective blocking of the cervical 3, 4, and 5 nerve roots shows promise in clavicle surgery, with its fast onset, good anesthesia and less complications, necessitating evaluation of its impact on diaphragmatic function. The purpose of this study is to examine the safety of C3, 4, and 5 nerve root block for its application in clavicle surgery. We conducted a pragmatic, randomized trial to evaluate the effect of C3, 4, and 5 nerve root block as compared with interscalene with intermediate cervical plexus block in diaphragmatic motion. This study involved forty patients undergoing right clavicle surgery. Patients were assigned in a 1:1 ratio to either a C345 nerve root block (administered with 2, 3, and 5 ml of 0.5% ropivacaine) or an interscalene with intermediate cervical plexus block (ISB + ICPB, each receiving 10 ml of 0.5% ropivacaine). Diaphragmatic kinetics were quantitatively assessed using sonographic techniques. The primary outcome was the incidence of complete hemi-diaphragmatic paralysis, observed at 30 min post-blockade. Secondary outcomes included the rate of complete hemi-diaphragmatic paralysis at 15 min and the degree of diaphragmatic motion restoration at 2, 4, 6, and 8 h post-blockade, onset time of block, motor block score in upper extremity, and adverse events. Results showed that only one patient (5%) in the C345 group vs. fifteen (75%) in the ISB + ICPB group experienced complete hemi-diaphragmatic paralysis at 30 min during deep breathing (P = 0.001). No patients in the C345 group, compared to five (25%) in the ISB + ICPB group exhibited paradoxical movement at 30 min during voluntary sniffing (P = 0.0471). Additionally, the C345 group demonstrated significantly greater diaphragmatic motion and upper limb strength restoration at all measured intervals post-blockade. Moreover, faster onset time and less adverse events were observed in the C345 group vs. in the ISB + ICPB group. Benefit from low volume of local anesthetics, the C345 nerve root block not only significantly reduces the incidence of complete hemi-diaphragmatic paralysis but also facilitates better recovery from diaphragmatic paralysis compared to the ISB + ICPB. It can be inferred that C345 is a more beneficial anesthesia method for early recovery of clavicular patients. Trial registration number: ChiCTR2300078283 04/12/2023.